Adding Value to Goat Meat: Biochemical and Technological Characterization of Autochthonous Lactic Acid Bacteria to Achieve High-Quality Fermented Sausages - Nediani, Miriam T. (2017)
Quality and safety are important challenges in traditional fermented sausage technology. Consequently, the development of a tailored starter culture based on indigenous microbiota constitutes an interesting alternative. In the present study, spontaneously fermented goat meat sausages were created and analyzed using a physicochemical and microbiological approach. Thereafter 170 lactic acid bacteria (LAB) strains were isolated and preliminary characterized by phenotypic assays. The hygienic and technological properties, and growth and fermentative potential of isolates using a goat-meat-based culture medium were evaluated. All strains proved to have bioprotective features due to their acidogenic metabolism. Almost all grew optimally in meat environments. LAB isolates presented proteolytic activity against meat proteins and enriched amino acid contents of the goat-meat-based model. The most efficient strains were four different Lactobacillus sakei isolates, as identified by genotyping and RAPD analysis. L. sakei strains are proposed as optimal candidates to improve the production of fermented goat meat sausages, creating a new added-value fermented product.